Protein Kinase A Associates with HA95 and Affects Transcriptional Coactivation by Epstein-Barr Virus Nuclear Proteins - Han, Innoc (American Society for Microbiology, 2002)
HA95, a nuclear protein homologous to AKAP95, has been identified in immune precipitates of the Epstein-Barr virus (EBV) coactivating nuclear protein EBNA-LP from EBV-transformed lymphoblastoid cells (LCLs). We now find that HA95 and EBNA-LP are highly associated in LCLs and in B-lymphoma cells where EBNA-LP is expressed by gene transfer. Binding was also evident in yeast two-hybrid assays. HA95 binds to the EBNA-LP repeat domain that is the principal coactivator of transcription. EBNA-LP localizes with HA95 and causes HA95 to partially relocalize with EBNA-LP in promyelocytic leukemia nuclear bodies. Protein kinase A catalytic subunit α (PKAcsα) is significantly associated with HA95 in the presence or absence of EBNA-LP. Although EBNA-LP is not a PKA substrate, HA95 or PKAcsα expression in B lymphoblasts specifically down-regulates the strong coactivating effects of EBNA-LP. The inhibitory effects of PKAcsα are reversed by coexpression of protein kinase inhibitor. PKAcsα also inhibits EBNA-LP coactivation with the EBNA-2 acidic domain fused to the Gal4 DNA binding domain. Furthermore, EBNA-LP- and EBNA-2-induced expression of the EBV oncogene, LMP1, is down-regulated by PKAcsα or HA95 expression in EBV-infected lymphoblasts. These experiments indicate that HA95 and EBNA-LP localize PKAcsα at nuclear sites where it can affect transcription from specific promoters. The role of HA95 as a scaffold for transcriptional regulation is discussed.